Removal of fluoride and natural organic matter from natural tropical brackish waters by nanofiltration/reverse osmosis with varying water chemistry. (February 2019) - Owusu-Agyeman, Isaac; Reinwald, Michael; Jeihanipour, Azam; Schäfer, Andrea Iris
Abstract: In the context of decentralised brackish water treatment in development applications, the influence of water quality on membrane separation was investigated with real waters. High ionic strength (low net driving pressure) on fluoride (F) retention by nanofiltration (NF) and reverse osmosis (RO) was investigated over a wide pH range (2–12). Further, the influence of pH on the permeation of natural organic matter (NOM) fractions, in particular low molecular weight (LMW) neutrals, was elucidated. Natural and semi-natural waters from Tanzania with similar F concentrations of about 50 mg L −1 but varying NOM and inorganic carbon (IC) concentration were filtered with an NF and RO, namely NF270 and BW30. F retention by NF270 for the feed water with highest ionic strength and IC concentration was lower and attributed to charge screening. This parameter further reduced at high pH due to co-ions (F − and CO3 2− ) interactions and combined (synergistic) effect of high salt concentration and pH on F. High NOM resulted in higher membrane zeta potential in comparison with low NOM natural water. However, there was no significant difference in F retention due to the fact that F retention enhancement was annulled by deposit formation on the membrane. The fraction of NOM found in NF/RO permeates was dominated by LMW neutrals. This was attributed to their size and uncharged nature, while their higher concentration at low pH remains unexplained. More humic substances (HS) of higher molecularity and aromaticity permeated the NF270 when compared with BW30, which can be explained with the different membrane molecular weight cut off (MWCO). The study highlights the complexity of treating tropical natural waters with elevated F and NOM concentrations. In order to develop appropriate membrane systems that will achieve optimal F and NOM removal, the influence of water quality parameters such as pH, NOM content, ionic strength and IC concentration requires understanding. Seasonal variation of water quality as well as operational fluctuations, which occur in particular when such treatment processes are operated with renewable energy, will require such challenges to be addressed. Further, given the high permeability of low molecular weight (LMW) organics significant permeate side fouling may be expected. Highlights: Real tropical waters with different IS, IC, NOM but similar F content treated by NF/RO. At high IS & pH, F retention decreases due to IC speciation, pH and salt effect. No enhancement effect of high NOM on F retention was observed. A discrepancy between permeate NOM measured by TOC analyser and LC−OCD was observed. According to LC−OCD results, LMW neutrals accounted for 60–90% of permeate NOM.